Global and national REDD+ architecture: linking institutions and actions - Wertz-Kanounnikoff, Shiela; Angelsen, A. (Center for International Forestry Research, 2009)
The global REDD+ architecture will influence the design and implementation of national REDD+ schemes. However, the nature of the global architecture is not yet clear and will probably evolve quickly over the next few years. To deal with uncertainties, countries should adopt flexible mechanisms and can implement REDD+ schemes in stages. Realising REDD+ within countries means paying attention to three key elements: incentives, information and institutions (the 3Is). Incentives consist of performance-based payments and changes in policies. Countries need to provide reliable information on realised changes in forest carbon stocks to qualify for funds from international sources. Effective institutions are needed to manage information and incentives. REDD+, as part of nationally appropriate mitigation action (NAMA), offers opportunities to harmonise national mitigation actions across sectors and to redirect development toward low carbon economies.